2017
DOI: 10.1016/j.socscimed.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical and mental health: A mediation analysis

Abstract: There is a strong link between mental health and physical health, but little is known about the pathways from one to the other. We analyse the direct and indirect effects of past mental health on present physical health and past physical health on present mental health using lifestyle choices and social capital in a mediation framework. We use data on 10,693 individuals aged 50 years and over from six waves (2002-2012) of the English Longitudinal Study of Ageing. Mental health is measured by the Centre for Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
389
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 661 publications
(434 citation statements)
references
References 45 publications
34
389
2
9
Order By: Relevance
“…A cohort study from Sweden also found that, in later life, older people who more engaged in more valued social activities were more socially active and physically active, therefore more reported less functional disability [7]. Our study showed that a higher level of social connection was associated with better elderly functional ability, as supported by previous studies reporting that more social connection linked to less likely to have functional limitations [38,39].…”
Section: Discussionsupporting
confidence: 86%
“…A cohort study from Sweden also found that, in later life, older people who more engaged in more valued social activities were more socially active and physically active, therefore more reported less functional disability [7]. Our study showed that a higher level of social connection was associated with better elderly functional ability, as supported by previous studies reporting that more social connection linked to less likely to have functional limitations [38,39].…”
Section: Discussionsupporting
confidence: 86%
“…For example, changing perceptions of aging might have favorable effects on emotional health and functional status. Further, a recent longitudinal study demonstrated that the relationship between depressive symptoms and ADLs (and vice-versa) was mediated by health behaviours and social engagement (Ohrnberger et al, 2017), suggesting that…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…30,31 Finally, need factors most relevant to MHL would be indicators of mental health such as exhibition of symptoms or diagnosis of mental illness and use of mental illness services as well as general health status since physical health and mental health are often correlated. [32][33][34]…”
Section: Introductionmentioning
confidence: 99%